Male Circumcision: A Practice Survey from Saudi Arabia - Osama A. Bawazir,; Hatem A. Sembawa, (Journal of King Abdulaziz University: Medical Sciences, 2019)
The study aims to evaluate the various techniques used to perform circumcision in Saudi Arabia. In September 2018, this cross-sectional survey was performed. A questionnaire was sent to all pediatric surgery units across the Kingdom. The responses to the questionnaire were analyzed and categorized. A total of 176 questionnaires were send and more than half (56.3%) of the practitioners filled the questioners, 62 (63%) were consultants, 19 (19%) were specialists and 19 (19%) were trainee in pediatric surgery fellowship program. Circumcisions were performed in Maternity and Children hospitals (32.3%), tertiary hospitals (32.3%), private hospitals (16%) and in general or academic hospitals (19%). The most commonly used method for circumcision was Gomco clamp (n = 39; 39.6%) followed by Plastibell (n = 30; 30%) and bone cutter (n = 25; 25.4%). The optimal time for circumcision was in neonatal period. Eighty-six percent of the surgeons agree that 2.5 to 5 kg is the optimal weight for the baby to do circumcision. In Saudi Arabia circumcision is a religious practice done for every Muslim male. It should be done by trained medical practitioner and circumcision done by non-medical personal should be avoided. Circumcision should be performed in the neonatal period and attention should be given to analgesia.